Management of Postpartum Haemorrhage With Uterine Balloon Tamponade: The Way Forward. Issue 2 (June 2016) - Marasinghe, J.P.; Du Plessis, J.; Epitawela, D.; Umstad, M.P.
Abstract : ( Aust N Z J Obstet Gynaecol . 2015;55(4):315–317) Uterine atony is the leading cause of postpartum hemorrhage, which is the sixth most common cause of maternal death in the United Kingdom. There are many methods for managing postpartum hemorrhage, but if conservative treatment does not work, surgical intervention should be used before the situation becomes severe. Uterine balloon tamponade (UBT), introduced in 1991, is one of the most popular early surgical interventions, due to its relative simplicity and ease of use.